PENGARUH TERPAAN KAMPANYE STOP PELECEHAN SEKSUAL DAN INTENSITAS KOMUNIKASI PEER GROUP TERHADAP SIKAP PENUMPANG PEREMPUAN DALAM MENGHADAPI TINDAK PELECEHAN SEKSUAL DI ARMADA TRANSJAKARTA - Putri Nabila, Alifia; Nugroho, Adi; Lukmantoro, Triyono (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The existence of sexual assault on public transportation is proof that security in public spaces has not been fully realized, especially for women who tend to be victims. Transjakarta, one of the public transportation companies in DKI Jakarta, is holding a Stop Sexual Harassment Campaign to create a safe space involving passenger participation. Peer group communication is one of the factors that can influence female passengers to have a firm attitude in dealing with sexual harassment in Transjakarta. This research aims to determine the influence of exposure to the stop sexual harassment campaign in Transjakarta and the intensity of peer group communication from the Busway Fan Club community in shaping the attitudes of female passengers facing acts of sexual harassment in Transjakarta. This research uses purposive sampling with a total of 100 respondents. The theories used in this research are Cognitive Response Theory and Reference Group Theory. Testing uses simple linear regression analysis. The findings show that there is an influence from exposure to the stop sexual harassment campaign and the intensity of peer communication from groups from the Busway Fan Club (BFC) community on the attitudes of female passengers in facing acts of sexual harassment in Transjakarta. These findings show that cognitively, affectively, and conatively, female passengers tend to act assertively if they see or become victims of sexual harassment in Transjakarta.